2021
DOI: 10.1007/s10668-021-01407-y
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable agricultural practices, farm income and food security among rural households in Africa

Abstract: Sustainable agriculture has been recognized in the literature as one of the important pathways to ensuring food systems and livelihoods among rural households in Africa. Using data from the 'Intensi cation of Food Crops Agriculture in Sub-Saharan Africa (Afrint)' project, we examine the impact of adoption of multiple sustainable agricultural practices (SAPs) -zero-tillage, intercropping, residue incorporation and animal manure -on farm incomes and food security (captures as self-su ciency in food production-SS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…CP (gross cereal production index) in Asia has been shown to reduce PUN (-0.009%). Increased agricultural production has been shown to increase food availability and income, thereby increasing food security and decreasing PUN (Abdallah et al 2021). Furthermore, CP does not affect PUN in Africa and LAC because it is influenced not only by food availability but also by the ease of food access (Nugroho et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…CP (gross cereal production index) in Asia has been shown to reduce PUN (-0.009%). Increased agricultural production has been shown to increase food availability and income, thereby increasing food security and decreasing PUN (Abdallah et al 2021). Furthermore, CP does not affect PUN in Africa and LAC because it is influenced not only by food availability but also by the ease of food access (Nugroho et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Research indicates that adopting multiple sustainable agricultural practices (SAPs) in Africa simultaneously results in higher farm income and improved food security for rural households, outperforming single-practice adoption or non-adoption. Households with at least three SAPs experience significantly higher farm income and enhanced food security than those implementing fewer than three practices (Abdallah et al, 2021). The research found that adopting at least three SAPs (improved seed, fertilizer, and soil and water conservation) positively impacted farm income and food security more than adopting one or two SAPs (Setsoafia et al, 2022).…”
Section: Sustainable Agricultural Practices and Traditional Knowledgementioning
confidence: 88%
“…As Kumar et al (2023) point out that "investment in development of entrepreneurial skills may impact positively on the economic growth of the country". Abdallah et al (2021) state that sustainable agricultural practices increase farm income and food security. Zhu et al (2022) also emphasis about social and economic transformations that have a profound impact on farmers' livelihood strategies, and changes in these strategies...…”
Section: Significant Of the Researchmentioning
confidence: 99%